Designing Business Model for Developing Micro Enterprise (Case Study Seluang Fish Fried of Ayakh Ugan) - Novy Anggraini; Rini Apriyani (Sustainable Business and Society in Emerging Economies, 2019)
The purpose of this study was to describe a business model that can be applied to the Seluang Fish Fried product of the Ayakh Ugan brand in Baturaja, Indonesia. The data was collected by using an interview with the owner and observation. The results analysis with the mapping of the canvass business model and blue ocean strategy. The application of these two combinations generates an overview of new strategies that can be applied to increase sales. From the result can be concluded elements that play an important role and can be improved, namely the value proposition, channels, revenue streams, key activities, and cost structures. The second step that needs to be reduced is dependence on the connector. In the third step, there are no elements that need to be eliminated. Then the final step on the elements of the value proposition, customer relations, main resources, and cost structure are the points that need to be created. This research provides an overview of the mapping of business models that can be applied to micro business products. this study is useful for business owners in creating new strategies to expand marketing and increase sales through the results of mapping methods that can be improved and created from important elements. This result can also be taken into consideration for other micro business owners to apply to their businesses.